1987
DOI: 10.1037/0021-843x.96.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Depressed patients have atypical hemispace biases in the perception of emotional chimeric faces.

Abstract: The perception of chimeric faces was studied in depressed patients in light of the presumed righthemisphere mediation of this function and evidence for right-hemisphere disorganization in major depression. Subjects were 27 unipolar depressive (Research Diagnostic Criteria) and 29 normal control right-handed male adults. Subjects performed a perception task that requires an emotional judgment about chimeric faces during free-field viewing and provides an index of hemispace bias (Levy, Heller, Banich, & Burton, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 18 publications
(33 reference statements)
7
42
2
Order By: Relevance
“…Heller et al (1995) suggested that differences among right-handers in magnitude of hemispatial bias for chimeric faces provide a measure of characteristic asymmetry of parietotemporal activation. They found depression to be associated with reduced right hemisphere bias for processing chimeric faces, consistent with evidence of impairments of right parietotemporal function in depressed patients (Bruder et al, 1989;Jaeger et al, 1987;Miller, Fujioka, Chapman, & Chapman, 1995). In a model proposed by Heller (1993), a right parietotemporal system is involved in the arousal component of emotion and in regulation of autonomic functions.…”
Section: Discussionmentioning
confidence: 66%
“…Heller et al (1995) suggested that differences among right-handers in magnitude of hemispatial bias for chimeric faces provide a measure of characteristic asymmetry of parietotemporal activation. They found depression to be associated with reduced right hemisphere bias for processing chimeric faces, consistent with evidence of impairments of right parietotemporal function in depressed patients (Bruder et al, 1989;Jaeger et al, 1987;Miller, Fujioka, Chapman, & Chapman, 1995). In a model proposed by Heller (1993), a right parietotemporal system is involved in the arousal component of emotion and in regulation of autonomic functions.…”
Section: Discussionmentioning
confidence: 66%
“…Concomitant electrophysiological recordings also showed differing lateralization patterns between the two groups. Jaeger, Borod, and Peselow (1987) also found that clinically depressed subjects had a significantly lower left hemispace bias than nondepressed subjects on ratings of freely viewed happy chimeric faces. This implies that the right hemisphere had less of an advantage on the chimeric face task in the clinically depressed than nondepressed subjects.…”
Section: Methodological Considerationsmentioning
confidence: 85%
“…The potential benefits of Web administration include increased sample size, increased sample diversity, and the ability to test participants with relatively rare neurological disorders. The importance of these factors is suggested by studies that have found that asymmetry scores on chimeric faces tasks are related to cognitive and personality measures (Rueckert & Pawlak, 2000), depression (David & Cutting, 1990;Jaeger, Borod, & Peselow, 1987;Kucharska-Pietura & David, 2003), and schizophrenia (David & Cutting, 1990;KucharskaPietura, David, Dropko, & Klimkowski, 2002).…”
Section: Discussionmentioning
confidence: 99%